Dolphin whistle repertoires around São Miguel (Azores): Are you common or spotted?. (April 2020) - Gannier, Alexandre; Fuchs, Sandra; Gannier, Adrien; Fernandez, Marc; Azevedo, José M.N.
Abstract: Short-beaked common dolphins ( Delphinus delphis ) and Atlantic spotted dolphins ( Stenella frontalis ) are both common in the Azores archipelago during summer. Because both species are sympatric, at least in part of their range, they may use acoustic features to recognize conspecifics and maintain school cohesion throughout their different activities. Delphinid whistles were recorded with a 96-kHz sampling rate using towed hydrophone system during surveys held in summer of 2013 and 2014 around São Miguel Island (Azores, Portugal). A total of 256 whistles attributed to either short-beaked common dolphin (n = 133) or Atlantic spotted dolphin (n = 123) were selected and processed with a contour extraction software. Elementary statistical analysis showed that duration, frequency and slope variables were significantly different for both species, although in most cases their range overlapped. We performed a discriminant analysis to test species classification: the dataset was randomly split into one calibration subset (186 whistles) and one validation subset (70 whistles). The discriminant analysis retained four variables (global slope, duration, minimal and final frequencies) as useful for classification. The discriminant function resulted in correct classification rates of 78.5% (calibration subset) and 81.4% (validation subset). Common dolphin whistles were better classified than Atlantic spotted dolphin whistles (83.4% and 74.8%) respectively. This study shows that reliable species identification can be achieved for common and spotted dolphins using their whistle repertoire characteristics.